Profil de l’endométriose pelvienne à l’IRM à Dakar - Sénégal - DIALLO Moustapha; NIANG Fallou Galas; DIOP Abdoulaye Dione; SOKO Thierno Omar; FALL Amat; DIOUF Cheikh Tidiane; MBENGUE Ababacar; NDIAYE Abdourahmane; DIOP Abdoulaye Ndoye; DIAKHATE Ibrahima (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2020)
Purpose: to describe the features and locations of pelvic endometriosis in MRI.patients and methods: This was a single-center, retrospective study of 47 cases of pelvic endometriosis over a 27-month period. The examinations were performed with a phased array surface antenna with a 1.5 Tesla high field MRI. The variables studied were age, indication of MRI, aspects and location of endometriosis. A simple entry of texts and tables was done on Excel and Word of Microsoft Office 2016.Results: The average age of the patients was 39.5 years (18 and 55). The clinical indications were dominated by pelvic pain (18 cases or 38%) followed by menstrual cycle disorders (10 cases or 21%). Adenomyosis was found in 32 patients (52,5%), associated with myomas in 15 cases. Ovarian endometriosis was observed in 9 patients (14,7%) with unilateral endometrioma in three patients and bilateral in six patients with a typical appearance of "kissing ovaries" in five cases. Deep endometriotic lesions were identified in 12 patients (19,7%) including 5 cases of uterine torus, 4 cases of uterosacral ligaments, 2 cases of rectovaginal septum involvement and 1 case of digestive tract involvement. Two cases of involvement of the anterior abdominal wall and three cases of hematosalpinx were noted. No case of superficial endometriosis has been identified. Multifocal involvement affected 14 patients (29,8%)Conclusion: endometriosis affects young women with a predominance of adenomyosis frequently associated with myomas. The site of the damage is variable with multifocal localizations in almost 30% of patients. RÉSUMÉ  Objectif : décrire les caractéristiques et les localisations de l’endométriose pelvienne à l’IRM. Patientes et méthodes : Il s’agissait d’une étude transversale monocentrique portant sur 47 cas d’endométriose pelvienne colligés sur une période de 27 mois. Les examens étaient effectués avec une antenne de surface en réseau phasé avec une IRM haut champ de 1,5 Tesla. Les variables étudiées étaient l’âge, l’indication de l’IRM, l’aspect et la localisation de l’endométriose. Résultats : l’âge moyen des patientes était de 39,5 ans avec des extrêmes de 18ans à 55ans. Les indications cliniques étaient dominées par les douleurs pelviennes 18 cas soit 38% suivies des troubles du cycle menstruel 10 cas soit 21%. L’adénomyose était retrouvée chez 32 patientes (52,5%). L’endométriose ovarienne était observée chez 9 patientes (14,7%) avec un endométriome unilatéral chez trois patientes et bilatérale chez six patientes avec un aspect typique de « kissing ovaries » dans cinq cas. Des lésions d’endométriose profonde étaient identifiées chez 12 patientes (19,7%) dont 5 cas du torus utérin, 4 cas des ligaments utérosacrés, 2 cas d’atteinte de la cloison recto-vaginale et 1 cas d’atteinte digestive. Deux cas d’atteinte de la paroi abdominale antérieure et trois cas d’hématosalpinx étaient notés. Aucun cas d’endométriose superficielle n’a été identifié. L’atteinte multifocale concernait 14 patientes (29,8%). Conclusion : L’endométriose pelvienne concerne la femme jeune avec une prédominance de l’adénomyose fréquemment associée à des myomes. Le site des atteintes est variable avec des atteintes multifocales chez près de 30% des patientes.